Related and unrelated diversification in crisis and in prosperity - Károly Miklós Kiss; László Lőrincz; Zsolt Csáfordi; Balázs Lengyel (Hungarian Academy of Sciences, Institute of Economics, 2018)
How does technological relatedness influence the portfolio of multi-product firms hit by external shocks? To answer this question, we look at the effect of product-specific demand shocks on product portfolios of Hungarian firms in the 2005-2012 period. We find that production have become more cohesive in terms of technological relatedness if firms were exposed to demand shocks. Evidence suggests that firms in crisis drop or downsize additional products not related to their core product and concentrate resources on related products.
Keywords: C23; D22; D24; L25; 330; product diversification; technological relatedness; industry space network; dynamics of product portfolio; crisis